SIRT2 and ALDH1A1 as critical enzymes for astrocytic GABA production in Alzheimer’s disease - Mridula Bhalla; Jinhyeong Joo; Daeun Kim; Jeong Im Shin; Yongmin Mason Park; Yeon Ha Ju; Park, Uiyeol; Seonguk Yoo; Hyeon, Seung Jae; Hyunbeom Lee; Junghee Lee; Ryu, Hoon; et al. (BioMed Central, 2025)
Background Alzheimer’s Disease (AD) is a neurodegenerative disease with drastically altered astrocytic metabolism. Astrocytic GABA and H2O2 are associated with memory impairment in AD and synthesized through the Monoamine Oxidase B (MAOB)-mediated multi-step degradation of putrescine. However, the enzymes downstream to MAOB in this pathway remain unidentified. Methods Using transcriptomics analysis, we identified two candidate enzymes, Aldehyde Dehydrogenase 1 family member A1 (ALDH1A1) and Sirtuin 2 (SIRT2) for the steps following MAOB in the astrocytic GABA production pathway. We used immunostaining, metabolite analysis and electrophysiology, both in vitro and in vivo, to confirm the participation of these enzymes in astrocytic GABA production. We checked for the presence of SIRT2 in human AD patients as well as the mouse model APP/PS1 and finally, we selectively ablated SIRT2 in the astrocytes of APP/PS1 mice to observe its effects on pathology. Results Immunostaining, metabolite analysis, and electrophysiology recapitulated the participation of ALDH1A1 and SIRT2 in GABA production. Inhibition of SIRT2 reduced the production of astrocytic GABA but not H2O2, a key molecule in neurodegeneration. Elevated expression of these enzymes was found in hippocampal astrocytes of AD patients and APP/PS1 mice. Astrocyte-specific gene-silencing of SIRT2 in APP/PS1 mice restored GABA production and partially improved memory function. Conclusions Our study is the first to identify the specific role of SIRT2 in reactive astrogliosis and determine the specific pathway and metabolic step catalyzed by the enzyme. We determine the partial, yet significant role of ALDH1A1 in this process, thereby highlighting 2 new players the astrocytic GABA production pathway. Our findings therefore, offer SIRT2 as a new tool to segregate GABA from H2O2 production, aiding future research in neurodegenerative diseases.